Rapid amino acid analysis of beers using flow-gated capillary electrophoresis coupled with side-by-side calibration. Issue 31 (21st July 2017) - Zhu, Qingfu; Zhang, Ning; Gong, Maojun
Abstract : Side-by-side calibration is enabled by alternate injections in flow-gated capillary electrophoresis to rapidly perform amino acid analysis, an important procedure to measure amino acids in various samples. Abstract : Amino acid analysis is an important procedure to measure free amino acids (AAs) in various samples including proteins, blood plasma, urine, foods and beverages. Due to the complexity of these samples, chemical separations are required to determine the composition and quantities of AAs. Here, we report a fast and accurate approach to quantify AAs in beers. This method was based on a flow-gated capillary electrophoresis (CE) system coupled with alternate injections enabled by a micro-fabricated switch. AAs in beer samples and standard solutions were fluorogenically derivatized with 2, 3-naphthalenedicarboxaldehyde (NDA) in the presence of cyanide. The two derivatized mixtures were then loaded into two separate micro-syringes and were alternately delivered to the flow gate for rapid injections and separations. Here, the standards functioned as side-by-side calibration and quantitation references. The separation of 21 AA derivatives was achieved within 90 seconds under an electric field of 1470 V cm −1 by using optimized background electrolytes consisting of 40 mM sodium tetraborate, 60 mM sodium dodecyl sulfate, and 2 mM 2-hydroxypropyl-β-cyclodextrin, and theoretical plates of >300k for most AAs were obtained. The beer matrix effect was studied, and the quantitation of AAs was conducted by directly comparing the peak heights of analytes with those of their individual self-standards. The method was validated with respect to the linearity, precision, and accuracy, and was applied to the measurements of 21 AAs in eight different beer samples. The results demonstrated the quantitative capability of flow-gated CE coupled with alternate injections for side-by-side calibration that was able to compensate for potential drift of the CE system. The developed method is expected to be valuable for high-throughput amino acid analysis of a variety of samples.